Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Model Pembelajaran Radec Berbantuan Book Creator pada Materi Teks Pidato - Anggi Putri Simorangkir; Rita Rita; Ali Ali (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study addresses the need for innovative and effective instructional materials in language learning by developing and evaluating Student Worksheets based on the Read, Answer, Discuss, Explain, and Create learning model integrated with the Book Creator digital platform for speech text instruction. Employing a Research and Development approach, the study applied the Four-D model encompassing the stages of Define, Design, Develop, and Disseminate. The research involved a population of 183 eighth-grade junior high school students, with a purposive sample of 31 students from class VIII-3. Data were collected through observations, interviews, questionnaires, and documentation, and analyzed using qualitative and quantitative techniques. Expert validation results indicated a high level of feasibility, with material validation reaching 84.8 percent and media validation 86.8 percent, both categorized as very feasible. Empirical findings further demonstrated strong effectiveness, reflected in positive teacher responses at 92 percent, student responses at 90 percent, and an average student learning achievement score of 90. These results substantiate that the developed worksheets are pedagogically sound and effective in enhancing student engagement and learning outcomes in speech text instruction.